Optimal Design of Inlet Passage for Waterjet Propulsion System Based on Flow and Geometric Parameters - Weixuan Jiao; Li Cheng; Di Zhang; Bowen Zhang; Yeping Su; Chuan Wang (Advances in Materials Science and Engineering)
As an important overcurrent component in a waterjet propulsion system, the inlet passage is used to connect the propulsion pump and the bottom of the propulsion ship. The anticavitation, vibration, and noise performance of the waterjet propulsion pump are significantly affected by the hydraulic performance of the inlet passage. The hydraulic performance of the inlet passage directly affects the overall performance of the waterjet propulsion system, thus the design and optimization method of the inlet passage is an important part of the hydraulic optimization of the waterjet propulsion system. In this study, the hydraulic characteristics of the inlet passage in the waterjet propulsion system with different flow parameters and geometric parameters were studied by a combination of numerical simulation and experimental verification. The model test was used to verify the hydraulic characteristics of the waterjet propulsion system, and the results show that the numerical results are in good agreement with the test results. The numerical results are reliable. The hydraulic performance of the inlet passage is significantly affected by the inlet velocity ratio. There is a certain correlation between the hydraulic performance of the inlet passage and ship speed, and the hydraulic performance of the inlet passage is limited by ship speed. The geometric parameters of the best optimization case are as follows: the inflow dip angle α is 35°, the length L is 6.38D0, and the upper lip angle is 4°. The optimal operating conditions are the conditions of IVR 0.69–0.87.